Migration and Histologic Effects of Visible Implant Elastomer (VIE) and Passive Integrated Transponder (PIT) Tags in the Marine Toad (Rhinella marina) - Megan L. Cabot (MDPI AG, 2021)
Passive integrated transponder (PIT) and visible implant elastomer (VIE) tags are commonly used to identify reptiles, amphibians, and fish. Despite reports of good retention rates and little to no negative effect on survival time, migration remains a concern and histologic changes have not been widely evaluated. Fifty-six wild-caught marine toads (Rhinella marina) were marked with a PIT tag in the left caudal thigh and a VIE tag over the right gastrocnemius muscle prior to transport to the North Carolina Zoo. Fourteen toads were then humanely euthanized on day 9, 15, 32, and 62 for postmortem examination and histopathology which were compared to 10 control toads with no tags. All PIT tags were functional and 95% remained at the insertion site with minimal to no histologic changes. Externally, 48% of VIE tags were visible through the skin at the original site of injection under fluorescent or UV light. Upon gross examination of the tissues, VIE tags had an overall retention rate of 62% at the injection site, with similar retention rates across time points. Migrated VIE material was visible grossly and histologically in the kidneys of 98% of toads and along the right leg, proximally and distally, in 25% of toads. VIE material was also found sporadically in mesentery, colon, and free in the coelomic cavity. Histologically, VIE material in the skin was surrounded by minimal to mild granulomatous inflammation while in the kidney it was associated with dilation of the small vessels, edema, and granulomatous nephritis that progressed in severity over time. Based on these findings, the authors recommend the use of PIT tags over VIE tags for identification of adult anurans, when feasible.